Translating, Narrating and Constructing Images in Journalism with a Test Case on Representation in Flemish TV News - Van Doorslaer, Luc (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2012)
This contribution develops a framework for research dealing with translation and localization in the media. It is stated that the borderlines between translation, localization and rewriting have become very blurred in the context of news production. Parallel to transediting, a term coined earlier, the concept of the journalator is presented, i.e., an interventionist newsroom worker who makes abundant use of translation when transferring and reformulating or recreating informative journalistic texts. By reference to both narrative theory and imagology, it is shown that the creation of national and cultural images occupies a special position in the intersections between translation studies, journalism studies and image studies. In the last part, the framework is complemented by a test case dealing with the representation of neighboring countries in Dutch-language Belgian (i.e., Flemish) TV news. It indicates that particularly the coverage of Germany is marked by specific topics and image building that were hypothesized before the analysis of the corpus.